STUDYING VOLATILITY IN SAUDI STOCK MARKET USING ARCH AND GARCH MODELS: A CASE STUDY OF AL RAJHI BANK - Almonifi, Yasser Saleh Ali; Alkhasi, Mohammed Murshed Ali; Sofian, Abdullah Saleh Ali (International Journal of Islamic Banking and Finance Research, 2023)
This study aims to empirically modeling the volatility of the daily closing share prices of Al-Rajhi Bank listed on Saudi stock exchange (Tadawul). The study approach related to quantitative method is based on the data collected through daily closing prices of Al Rajhi Bank shares for the period from 1/02/2018 to 9/23/2022. To analyze the data and test the study hypothesis, ARCH and GARCH models were applied in this paper. According to results of heteroskedasticity tests, values of R-squared, Akaike, Schwarz, and Hannan-Quinn of ARCH models, the GARCH (1, 1) model is suitable for describing the conditional variance and the estimation. The findings indicate that the positive shocks synchronizing with favorable conditions cause less severe fluctuations than the negative shocks synchronizing with unfavorable conditions. The research has some limitations that must be noted in terms of the study sample which represents only Islamic banks and therefore, the results cannot be generalized to other banks, similarly, the heterogeneity of banks in terms of the size of assets and finance capabilities. This research emphasizes the importance of developing banking performance and enhancing investment strategies to enhance the stability of bank share prices, especially during crises. Based on the results, investors may have the incentive to buy shares of Islamic banks according to stock price indices characterized by stability in the face of economic shocks. This study is considered as one of the main studies contributing to the analysis of the volatility of the daily closing share prices of Islamic Banks listed on the Saudi stock exchange (Tadawul). JEL Classification Codes: E44, E58, G24, G18, H12.